2011
DOI: 10.1002/elan.201000755
|View full text |Cite
|
Sign up to set email alerts
|

A Selective Simultaneous Determination of Levodopa and Serotonin Using a Glassy Carbon Electrode Modified with Multiwalled Carbon Nanotube/Chitosan Composite

Abstract: A glassy carbon electrode (GCE) modified with carbon nanotube/chitosan (MWCNTs-CHT/GCE) was used for the sensitive voltammetric determination of levodopa (Lev) and serotonin (Ser). The measurements were carried out using cyclic voltammetry (CV), differential pulse voltammetry (DPV) and chronoamperometry (CA). Under the optimum conditions the electrode provides a linear response versus Lev and Ser concentrations in the range of 2.0-220.0 mM and 0.5-130.0 mM, respectively, using DPV. The modified electrode was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 67 publications
4
24
0
Order By: Relevance
“…4c). As seen in Table 1, compared with other electrochemical sensors for the determination of serotonin, the CNT-modified acupuncture needle obtained a low detection limit, which is comparable with that reported previously33343536373839.…”
Section: Resultssupporting
confidence: 86%
“…4c). As seen in Table 1, compared with other electrochemical sensors for the determination of serotonin, the CNT-modified acupuncture needle obtained a low detection limit, which is comparable with that reported previously33343536373839.…”
Section: Resultssupporting
confidence: 86%
“…This peak is attributed to an irreversible oxidation of the hydroxyl group present in the aromatic ring of the serotonin forming ketone species. 34 The Au/ssDNA/SWCNT surface caused a shift of 140 mV in the oxidation potential of serotonin to a less positive value when compared to the bare Au electrode (+540 mV). Additionally, the oxidation on such a catalytic surface showed a 3-fold increase in peak current compared to the unmodified one.…”
mentioning
confidence: 99%
“…Serotonin has been determined by several techniques, which integrate separation methods-such as liquid chromatography [36][37][38] and capillary electrophoresis 39 -or direct assays using potentiometry 27,29,40 and sensor-based applications. 41,42 In general, as verified in Table 1, our set up shows a LOD lower than those reported in the literature even when a preconcentration step was employed.…”
mentioning
confidence: 99%
“…For electrosynthesizing the MWNT-PINA com posite coating, we used a suspension containing (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) The deposition of these films on the GC electrode surface was carried out at the supersonic treatment (35 kHz). After the preparation of modified elec trodes, they were thoroughly washed with twice dis tilled water and immersed into PB.…”
Section: Electrosynthesis Of the Polymer Film And Preparation Of Compmentioning
confidence: 99%
“…Several fundamental publications in this field dealt with electrochemical determination of catecola mines, predominantly DA, with the use of electrodes modified by micro or nanoparticles of carbon and various metals or metal compounds. It was shown that in this case, the high sensitivity and selectivity of trans fer on the target components could often be achieved at the total high level of permeability [3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 97%